Mathematical Model of the Ignition of a Gel Fuel Particle in a High-Temperature Air Medium; Russian Journal of Physical Chemistry B; Vol. 17, iss. 1 - Glushkov D. O. Dmitry Olegovich (2023, 2023)
Title screen